2012
DOI: 10.12693/aphyspola.121.546
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Human Osteoblast-Like MG 63 Cells Proliferation on Resorbable Polymer-Based Nanocomposites Modified with Ceramic and Carbon Nanoparticles

Abstract: Polymer-based nanocomposites containing biocompatible and bioactive nanocomponents seem to be excellent materials that could be used in many biomedical applications. The aim of this study was biological evaluation of resorbable polymer-based nanocomposites (PLA, PCL) and their modifications with ceramic nanoparticles (silica -SiO 2 , montmorylonit -MMT) or carbon nanotubes. The nanocomposites were seeded with the human osteoblast-like MG 63 cells. After 1, 3 and 7 days of incubation, Trypan blue exclusion test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…No significant difference in doubling time were seen among the surfaces examined (Ti-KC, 31.03 ±6 h and Ti-KF, 33.6 ± 6.4 h), which were similar to that seen (∼29 h) with culture on keratin sponges [23]. While studies have shown 1.3-1.9 times higher doubling times of MG-63 cells cultured on different substrates [37,38], the results of this study indicate that the growth rate of MG-63 cells on all surfaces was similar despite any poor initial cell attachment.…”
Section: Discussionsupporting
confidence: 72%
“…No significant difference in doubling time were seen among the surfaces examined (Ti-KC, 31.03 ±6 h and Ti-KF, 33.6 ± 6.4 h), which were similar to that seen (∼29 h) with culture on keratin sponges [23]. While studies have shown 1.3-1.9 times higher doubling times of MG-63 cells cultured on different substrates [37,38], the results of this study indicate that the growth rate of MG-63 cells on all surfaces was similar despite any poor initial cell attachment.…”
Section: Discussionsupporting
confidence: 72%
“…The PLA nanofibres are degrading in a biological environment with the time, and it may be expected to expose the surface of carbon nanotubes. The biological tests indicated that the samples containing carbon nanotubes were not toxic [51]. On the other hand, the presence of CNTs in PLA nanofibres modifies their mechanical and electrical properties.…”
Section: Resultsmentioning
confidence: 97%
“…It was previously reported that bone marrow‐derived stromal cells (BMSCs) on the composite scaffolds differentiated down the osteogenic lineage and expressed high levels of the bone marker ALP. It was confirmed that the PCL/CNT nanocomposites are appropriate for the growth and proliferation of the human osteoblast‐like cells []. Biodegradation experiments showed that PCL still holds its biodegradability and the CNTs hold on to their inherently tube‐like characteristic.…”
Section: Hybrid Bone Scaffolds For Maxillofacial Defects and Tissue Ementioning
confidence: 92%